Factors Causing Stress Among First-Year Bams Students (2022/2023) Of The University Of Colombo (A Pilot Study) - Wickramasinghe, N.K.W.; Munasinghe, D.A.L. (International Journal of Advance Research Publication and Reviews, 2026)
Stress is a prevalent concern among university students, with first-year undergraduates particularly vulnerable due to the transition from structured school environments to self-directed university learning. This pilot study investigates the prevalence and determinants of stress among first-year Bachelor of Ayurvedic Medicine and Surgery (BAMS) students at the Faculty of Indigenous Medicine, University of Colombo. A descriptive cross-sectional pilot study was conducted between June and August 2025 among 30 students selected through systematic random sampling. Data were collected using a pretested, self-administered questionnaire covering socio-demographics, academic workload, psychosocial factors, and personal experiences. Results indicated that moderate stress was predominant (50%), followed by high (33.3%), low (13.3%), and very high (3.3%) stress. Headache and dizziness were the most reported stress-related symptoms (43.3%), while examination periods were the primary stress trigger (56.7%). Stress was significantly associated with adjustment to university life, social relationships, perceived institutional support, feelings of being overwhelmed by academic workload, and financial difficulties. Academic workload alone was not a significant predictor. These findings highlight that stress among first-year BAMS students is multifactorial, with psychosocial and environmental factors playing a larger role than academic load alone. Interventions focusing on student support, stress management, and mentorship are recommended to promote mental wellbeing and academic success.
Keywords: Stress; BAMS students; academic workload; psychosocial factors; university adjustment; mental health